The relationship between students’ personality and their achievement in solving mathematics higher order thinking skills questions - Abdullah, Abdul Halim (Secholian Publication, 2023)
This study identifies the relationship between the personality traits and achievements in solving the mathematics HOTS questions of 254 Year Six students from three primary schools in Ulu Tiram. The findings from the personality questionnaire and the mathematics HOTS question paper were an-alysed. The findings showed that the main dominant personality traits of the students were the openness followed by extraversion, neuroticism and agreeableness. For the achievement in the HOTS paper, 61 students scored highly, 55 in the very high category, and the rest were in the very low, low and medium categories. The result of regression analysis showed that the predictor of the standardised predictive coefficient of the neurotic characteristic (ᵦ = −.132) was significant, while the correlation value of students’ achievement and neurotic personality trait was 0.132. This showed that the relationship between students’ neuroticism and their achievement in solving the mathe-matics HOTS question was very low. Therefore, only neuroticism out of the five types of personality traits contributed to the achievement of Year Six students in solving the mathematics HOTS ques-tion. Hence, the findings conclude that personality traits are not the main factor affecting the achievement of the Year Six students in solving mathematics HOTS questions.